Neurodevelopmental outcomes in young children born to HIV‐positive mothers in rural Yunnan, China. Issue 7 (20th June 2018) - Wu, Jie; Li, Jing; Li, Yan; Loo, Kek Khee; Yang, Haixia; Wang, Qiong; Duan, Rufei; Xiao, Xia; Song, Xiaoxiao; Yang, Siwei; Sun, Lin
Abstract: Background: Children born to HIV‐infected mothers are at risk for neurodevelopmental delay. Little is known about the neurodevelopmental outcomes of infants and toddlers born to HIV‐positive mothers but who were not themselves infected by HIV, especially in poor rural areas. This study was conducted to compare developmental outcomes between young children who were HIV exposed but uninfected (HEU), and their HIV unexposed and uninfected (HUU) peers in rural Yunnan, China. Methods: A total of 250 HEU children aged 6–36 months and 250 HUU children matched for age, gender and residency were recruited from rural Yunnan, China. Neurodevelopmental outcomes were measured using Bayley Scales of Infant and Toddler Development–Third Edition (Bayley III). Multivariate analysis was performed to adjust for potential confounding effects of caregiver demographic data, maternal health status, birth outcome and children's health status. Results: HIV exposed but uninfected children had significantly lower composite scores in Bayley III assessment than HUU children (in the cognitive domain: 90.34 vs 92.75, P <0.05; in the adaptive behavior domain: 77.04 vs 80.80, P < 0.05). On stepwise logistic regression analysis, HIV exposure (OR, 1.45; 95%CI: 1.04–1.98) and child malnutrition (OR, 1.67; 95%CI: 1.09–2.23) were risk factors for below‐average cognition development. Mother's low education and child anemia were significant risk factors for below‐average motor and adaptive behavior development. Conclusion: Perinatal HIV infection may have a negative impact on neurodevelopment in young children. Other factors such as mother's education and child nutrition status may play important roles in child neurodevelopment, especially in resource‐poor areas. Further studies are needed to examine the long‐term effect of perinatal HIV infection on later childhood neurodevelopment.